Libraries, Information and Nation Building in Africa - Doddoo, Victoria (Ghana Library Journal, 2003)
With particular reference to the African situation, this paper discusses the important role of libraries in nation building. Issues covered include the role of information on the educational, political and socio-economic development of nations. It also examines the impact of libraries in the development of literacy, and proposes the establishment of more oral documentation centres in Africa.